2019
DOI: 10.1111/cbdd.13579
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of peptides with enhanced antimicrobial and anti‐biofilm activities against cariogenic bacterium Streptococcus mutans

Abstract: Streptococcus mutans (S. mutans) is known to be a leading cariogenic pathogen in the oral cavity. Antimicrobial peptides possess excellent properties to combat such pathogens. In this study, we compared the antimicrobial activity of novel linear reutericin 6-and/or gassericin A-inspired peptides and identified LR-10 as the leading peptide. Antibacterial assays demonstrate that LR-10 is more active against S. mutans (3.3 μM) than many peptide-based agents without resistance selection, capable of killing many or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Jannadi et al [89] synthesized Pep19-2.5 and Pep19-4LF and assessed that they inhibited S. mutans growth and biofilm formation. Similarly, Zhang et al [39] designed DPS-PI, Liang et al [90] designed LR-10, Da Silva et al [91] designed [W7]KR12-KAEK, and all of their antibacterial activities were evaluated by assessing the inhibition of S. mutans growth and biofilm biomass, furthermore assessing the destruction to biofilm morphology and the damage to the bacterial surface via scanning electron microscopy. In this current study, GERM CLEAN showed capabilities on reducing the initial adherence and disrupting the biofilm formation of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…Jannadi et al [89] synthesized Pep19-2.5 and Pep19-4LF and assessed that they inhibited S. mutans growth and biofilm formation. Similarly, Zhang et al [39] designed DPS-PI, Liang et al [90] designed LR-10, Da Silva et al [91] designed [W7]KR12-KAEK, and all of their antibacterial activities were evaluated by assessing the inhibition of S. mutans growth and biofilm biomass, furthermore assessing the destruction to biofilm morphology and the damage to the bacterial surface via scanning electron microscopy. In this current study, GERM CLEAN showed capabilities on reducing the initial adherence and disrupting the biofilm formation of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…[22] In general, the antibacterial activity of AMPs is related to their hydrophobicity, that is, the higher the hydrophobicity, the stronger the antibacterial activity. [32] The results of our study revealed that the hydrophobic values of the four AMPs were in the following order: (LLKK) 3 L > G(LLKK) 3 L > (LLKK) 3 > G(LLKK) 3 , but the MIC value of the G(LLKK) 3 L AMP was lower than that of (LLKK) 3 L. This is due to the exceeding of a specific threshold by the hydrophobicity of AMPs, which may lead to the decrease of their antibacterial activity with the increase of their hydrophobicity. [33] The analysis of the antibacterial activity under the conditions of various physical and chemical factors can provide a reference for the use of AMPs, especially for protease stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has the specific targeting ability for hydroxyapatite (HA) but excludes the hydrolysis sites in statherin, which enables the stable and strong anchoring on the tooth surface in the complex oral environment. , In light of this, this sequence can be utilized to construct an adaptive functional layer by integration with other moieties . It is well documented that PEG-modified peptides could enhance the hydrophilicity, physicochemical, and biological stability of peptides, which not only protect the antimicrobial moieties from being masked or broken down but also attenuate the damage to the surrounding tissue mucosa. Moreover, targeting the acidic microenvironment has been reported to be efficient for dental caries prevention. A few studies have explored the adaptive antibacterial ability of histidine-rich antimicrobial peptides (AMPs) against cariogenic bacteria such as Streptococcus mutans (S. mutans). Considering that the arginine and tryptophan have functional groups similar to that of histidine, it was speculated that RWRWRW might possess pH-responsive antimicrobial effects under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%